No excess VO2 during whole-body high intensity exercise in well-trained cross-country skiers - Björklund, G.; Stöggl, T.; Holmberg, H. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Cross-country skiing competitions are performed close to 90% of VO2max (Mygind, Andersen, & Rasmussen, 1994). At this intensity O2 extraction is close to its maximum in both arms and legs (Björklund, Stöggl, & Holmberg, 2010). Consequently, there is a limited possibility to further increase VO2 at such a strenuous workload. However, an increased VO2 has been reported during constant running speeds above the lactate threshold (Jones, Carter, & Doust, 1999). The aim of this study was thus to investigate whether VO2 tends to increase during high intensity exercise that uses a large muscle mass. Methods: Eight XC skiers (age 22±3yr; VO2max 69±3 ml•kg-1•min-1, obtained during diagonal stride (DIA) on a treadmill) performed a continuous protocol, of 3-min at 90% of DIA1 VO2max, 3-min at 90% of double poling (DP) VO2peak and a 3-min bout at 90% of DIA2 VO2max. Cardio-respiratory data was obtained continuously and determination of blood gases and metabolites from a. femoralis, v. femoralis and v. subclavia. Pole and plantar forces measured (Pedar Mobile, 100Hz) and EMG data from six lower and upper body muscles (Noraxon, 3000 Hz). One and Two-Way ANOVA were used to analyze data between the three different workloads. Alpha was set a priori to 0.05. Results: VO2 for DIA1 90% VO2max, DP 90% VO2peak and DIA2 90% VO2max, were 4.89 ± 0.13, 4.36 ± 0.49 and 4.99 ± 0.11 respectively. Lactate increased between DIA1, DP, and DIA2 with a greater increase in the femoral artery and vein (P<0.05). O2 extraction was attenuated during DP (P<0.05) but remained constant during DIA1 and DIA2 (P>0.05). Sum average EMG and RMS over all muscles was lower during DP compared with DIA, with no difference between DIA1 and DIA2 (P<0.05). Peak pole force and RMS during DP was higher when compared to DIA (P<0.05). Discussion: VO2 was lower during DP compared to DIA, with no difference in VO2 between the DIA workloads although there was a great increase in venous blood lactate in arms and legs as well as arterial blood throughout the protocol. Therefore our results do not support increased VO2 above the lactate threshold when using a large muscle mass at a high exercise intensity. Muscle activation remained constant, as indicated by the absence of change in biomechanical characteristics, i.e. EMG in the indicator muscles, foot or plantar forces. The unchanged muscle activation along with VO2 suggests that the work economy remained constant. In conclusion, in well trained crosscountry skiers, VO2 does not increase over time when both arms and legs are highly activated.